DIGITALIZATION OF FINANCIAL REPORTING FROM MSME PERSPECTIVE IN MATARAM CITY - Jaka Anggara; Nungki Kartikasari (Laboratorium Riset Ekonomi, 2023)
This research explores the digitalization of financial reporting from the perspective of Micro, Small, and Medium Enterprises (MSMEs) in Mataram City. As digitalization increasingly transforms business processes, the study investigates the readiness and perception of MSMEs towards adopting technology for financial reporting. The government's emphasis on MSME growth and improved financial administration aligns with the challenges faced by these enterprises, including the absence of accounting information systems and reliance on manual techniques. The study involves 136 MSMEs in Mataram City, revealing that while a significant portion records cash transactions, less than 25% prepare formal financial reports. Additionally, a limited number have embraced digital tools for accounting purposes. Notably, 36.03% express willingness to provide online and real-time access to financial reports for external stakeholders. This research underscores the importance of digital financial reporting for MSMEs' effective financial management and decision-making. The findings highlight the existing gaps and opportunities for further integration of technology in MSMEs, emphasizing the need for awareness and education initiatives. Future research directions may explore alternative methodologies and additional perspectives, such as those from accounting professionals and government entities.